Improving Working Method of Label Cutting Station in the Jago Jaya Shuttlecock Industry for Increases Productivity: Perbaikan Metode Kerja Stasiun Pemotongan Label di Industri Shuttlecock Jago Jaya untuk Meningkatkan Produktivitas - Astuti, Rahmaniyah Dwi; Suhardi, Bambang; Iftadi, Irwan; Nadhira, Afra Galda; Syahliantina, Annisa (Procedia of Engineering and Life Science, 2023)
The process of cutting labels at the Jago Jaya Industry Shuttlecock has not implemented efficient working methods, so production targets are not achieved. This study aims to improve the working method of the workstation through the implementation of a label cutting tool in the Jago Jaya industry. The method used to analyze hand movements uses the Right Hand and Left Hand Map. Improved operator hand movements to be more balanced so as to increase productivity at the label cutting workstation. The time required to cut 50 labels was reduced from 72 seconds to 46 seconds after the application of the cutting tool and the change in the placement of the equipment closer to the operator. After the implementation of the pacemaker, the ineffective movements of the left hand were eliminated, such as 8 times from 10 to 2 times and 4 times from 6 to 2 times. Meanwhile, on the right, campaigns were held 1 time, from 5 times to 4 times.